Missing Gas-Phase Source of HONO Inferred from Zeppelin Measurements in the Troposphere - Xin Li; Rohrer, Franz; Hofzumahaus, Andreas; Brauers, Theo; Rolf Häseler; Bohn, Birger; Broch, Sebastian; Fuchs, Hendrik; Sebastian Gomm; Holland, Frank; Julia Jager; Jennifer Kaiser; et al. (Science, 2014)
Gaseous nitrous acid (HONO) is an important precursor of tropospheric hydroxyl radicals (OH). OH is responsible for atmospheric self-cleansing and controls the concentrations of greenhouse gases like methane and ozone. Due to lack of measurements, vertical distributions of HONO and its sources in the troposphere remain unclear. Here, we present a set of observations of HONO and its budget made onboard a Zeppelin airship. In a sunlit layer separated from Earth's surface processes by temperature inversion, we found high HONO concentrations providing evidence for a strong gas-phase source of HONO consuming nitrogen oxides and potentially hydrogen oxide radicals. The observed properties of this production process suggest that the generally assumed impact of HONO on the abundance of OH in the troposphere is substantially overestimated.